Aktivitas Analgesik Ekstrak Etanol Bulu Babi (ECHINOMETRA MATHAEI) Pada Mencit Putih Jantan - Lestiono, Lestiono; Kresnamurti, Angelica; Rahmad, Effendi; Ansyori, Muhammad Riko (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2020)
Sea urchin (Echinometra mathaei) is a potential marine resourches that had not been explored widely. It has flavonoid, triterpenoid, alkaloid, saponin compound with high antioxidant activity. Antioxidant activity and flavonoid compound were potentially correlated with analgesic activity. This study aimed to examine e the potential of Echinometra mathaei as an analgesic in white male mice that were induced by acetic acid to produce peripheral pain in vivo (streatching in mice) with writhing test method. The amount of stretching was observed for 1 hour after administration of ethanol extract of Echinometra mathaei orally. Balb/c white mice which devided into 6 groups randomlly, as negative control group, a group that induced acetic acid 1%, Asetosal group with dose of 65 mg/kgBW, and Echinometra Mathaei groups with the dose of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW. The results of this study showed that all dosage of Echinometra mathaei decrease the peripheral compared to negative control (P,0.05). The percentage inhibition of pain at 200 mg/kgBW (72.59%) was the highest among other doses was significant different from asetosal group (52.53%). This research concluded that Echinometra mathaei has the analgesic activity to inhibit peripheral pain . Keywords: Echinometra mathaei, ethanol extract, analgesic, mice, writhing test